Frekuensi Pemunculan, Tingkah laku, dan Diversitas Cetacea di Perairan sekitar Labuan Bajo, Flores, Nusa Tenggara Timur - Priscilla Princessa Amalo; I Dewa Nyoman Nurweda Putra; I Nyoman Giri Putra (Department of Marine Sciences, Faculty of Marine and Fisheries, Universitas Udayana, 2023)
At least 30 cetaceans live in Indonesia, especially in the eastern waters of Indonesia, consisting of whales and dolphins. Cetaceans play an important role as a key species in determining the health of marine ecosystems. This study aims to determine the frequency of appearance, behavior, and diversity of cetaceans along Labuan Bajo, Flores, and East Nusa Tenggara. The study was conducted in October-November 2021, with four weeks to collect field data and interviews. The data involved a ship carrying a group of observers consisting of four people, with each task assigned to look for the appearance, species, and behavior of cetaceans. In the interview methods, interviews were conducted with fishermen regarding the presence of cetaceans. The data was then processed using the Microsoft Excel program and later plotted using the ArcView program as the outpour of the cetacean distribution. The results showed 19 occurrences of cetaceans, with six occurrences found in the field survey and 13 based on interviews with fishermen. Appearances were found to be evenly distributed in the study area, with a total of 7 species of cetaceans found, namely Stenella longirostris, Stenella attenuata, Tursiops truncates, Pseudorca crassidens, Grampus griseus, Kogia simus, and Physeter macrocephalus. In species composition and abundance, S. longirostris species had the highest value, and the P. crassidens species had the lowest composition value. A value of 1.06 was found in diversity, indicating that the cetaceans in Labuan Bajo were classified as moderate. Some behaviors include aerials, spy hopping, bow-riding, feeding, and avoidance.